Scientific literacy: a key part of school contexts - Colonia Cerna, Stefanny (2021)
The work conducted a bibliographic review on alphabetization scientific, which is understood as the ability to use scientific knowledge in order to understand and help make decisions about the actual world. It also sought to explain the evolution of the dimensions of scientific literacy and to present theoretical proposals for methodological strategies to help improve it. Articles, doctoral theses and PIS test reports were reviewed to reach twoconclusions: 1) it is essential to develop the four dimensions of scientific literacy, because, in this way, scientifically literate students will be trained; that is, they are able to become world that goes through constant scientific and technological and 2) it is necessary to update the teaching-learning strategies by those that are part of the so-called active methodology such as discovery learning, research-based learning and project-based learning.